Pengaruh Media Pembelajaran Crosword Puzzle Dengan Model Discovery Learning Terhadap Hasil Belajar Siswa Pada Konsep Gelombang Bunyi Di SMAN 1 Boliyohuto - Iswanto A. Yunus; Raghel Yunginger; Mursalin Mursalin; Dewi Diana Paramata; Dewa Gede Eka Setiawan; Abdul Haris Odja (Department of Physics Education, Universitas Mataram, 2021)
This study aims to determine the effect of crossword puzzle learning media with discovery learning models on student learning outcomes on the concept of sound waves. This research is a quasi-experimental type of research using one class (one samples) only the experimental class using the One Group pretest posttest design. In this study, learning was conducted three times online with the discovery learning model. The instrument used in data collection is an essay test of learning outcomes. The method used to analyze the data is descriptive analysis technique, namely normality test, hypothesis testing with a significance level of 5%. Based on hypothesis testing using parametric statistics t test obtained tCalculate (5.789 > ttabel (2.024) with a significant level = 0.05. where hypothesis one (H_1) is accepted. This shows that there are differences in student learning outcomes before and after learning using learning media crossword puzzle with the discovery learning model. This result is also shown from the increase in student learning outcomes on the posttest test which is higher than in the pretest test with an average value of 76.03% and 65.71%. Thus the use of crossword puzzle media with the discovery learning model affects the results student learning